한국 남성의 신체 및 생화학 인자와 골밀도 : 2008~2011년 국민건강영양조사를 바탕으로 - 최순남; 조광현; 정남용; Choi, Soon-Nam; Jho, Kwang-Hyun; Chung, Nam-Yong (東아시아食生活學會誌, 2014)
This study investigated factors affecting the bone mineral density (BMD) of Korean adult men. Data on BMD and anthropometric (height, weight, body mass index, BMI, waist circumference, body fat) and biochemical(total cholesterol, vitamin D, alkaline phosphatase, ALP) measurements were obtained from the Fourth and Fifth Korea National Health and Nutrition Examination Surveys (KNHANES, 2008~2011). Overall, BMD of the subjects was decreased from year to year (T-score of 30~39 yr decreased to 0.447 (2010~2011) from 0.106(2008~2009) and in 50~59 yr decreased to 0.234 from 0.033. Age was negatively associated with BMD (T-score 0.361 of 20~29 yr group and -0.894 of ${≥}80yr$ group in total femoral). According to increase of weight, BMI and waist circumference continuously increased BMD. High value of total cholesterol (T-score 0.157 of 201~<230 mg/dL group and 0.064 of ${≥}230mg/dL$ group in total femoral) and alkaline phosphatase (T-score 0.337 of ${≤}102IU/L$ group and -0.270 of ${≥}336IU/L$ group in total femoral) were associated with lower BMD. Overall height, weight and BMI were positively associated with BMD, and ALP were negatively associated with BMD. Finding of the present study showed that bone loss may be associated with various factors such as age, weight, BMI, total cholesterol, vitamin D and ALP density and that much attention should be paid to bone health of adult men. Therefore, practical and systematic programs are required to improve the BMD of adult men as well as to maintain bone health.